How to lead major students to achieve organizational goals? an exploration - Nirtha, Eva; Hurit, Andreas Au; Tembang, Yonarlianto (Institute of Computer Science (IOCS), 2025)
Leadership in the major's student organization is a crucial factor in directing its members to achieve common goals. This research aims to explore how a leader can effectively lead students in the department to achieve organizational goals. Using a qualitative approach, data was collected through in-depth interviews, observations, and documentation of student organizational activities at the department level. The results of the study show that inclusive, participatory and transformational leadership styles, interpersonal communication skills, and an adaptive approach to group dynamics play an important role in organizational success. In addition, active involvement of members, clarity of vision, proportional division of roles and support from a number of department lecturers also strengthen the process of achieving goals. Therefore, this study aims to explore how the leadership carried out at HMJ PGSD Musamus University by the management of HMJ PGSD in the period 2024–2025 in order to achieve organizational goals.